Efektifitas Automasi Perpustakaan Terhadap Kualitas Pelayanan Publik Pada Perpustakaan Daerah Kota Payakumbuh - Dodi Nofri Yoliadi (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
This study aims to find out what is being done by the Payakumbuh City Library in developing a library automation system. Data collection is done using observation, interviews, and documentation. The results obtained that the Payakumbuh City Regional Library has carried out services in the form of empathy, vigilance, responsiveness, reliability, and certainty, the results show that there are several problems and deficiencies faced by the Payakumbuh City Library in providing services to the community. Lack of human resources that can hamper library services to the community, physical building facilities such as adequate library buildings. In the use of library automation systems, it is still not implemented in the library. It can be concluded that the community in response to library automation services in the Payakumbuh City area in both categories. Suggestions given for the top priority that must be made are the circulation of library web -based services more optimized and professional in providing services to the community.